Preparation method of catalyst for preparing formaldehyde
The octahedral defects and pores of the catalyst are formed by ultrasonic heating, and the introduction of MoO3 and sulfur elements are solved, the problem of iron-molybdenum catalyst deactivation is improved, the activity and stability of the catalyst is improved, and its life is extended.
Patent Information
- Application Number
- CN202311162720.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-11
AI Technical Summary
The existing iron-molybdenum catalysts will have different degrees of catalyst deactivation as the use time extends, resulting in a decrease in activity and a decrease in selectivity, which cannot fundamentally solve the catalyst life problem.
By using ultrasonic heating, part of the octahedral in the FeO6 octahedral population is twisted, octahedral defects are generated, and a channel is formed, and excess Mo is introduced at the junction of Fe2(MoO4)3 and MoO3 phases are formed to form MoO3 embedded in the lattice gap of the catalyst, resulting in lattice distortion and pore formation, increasing the lattice defect of the catalyst. At the same time, benzyl/sodium acetate and sulfur elements were introduced to form a conjugated system and inhibit deep oxidation reaction.
It effectively solves the problem of deep oxidation reaction of the catalyst, improves the activity and stability of the catalyst, and extends the life of the catalyst.
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalyst preparation, and in particular to a method for preparing a catalyst for preparing formaldehyde. Background Art
[0002] Formaldehyde is an important basic organic chemical raw material, which plays a decisive role in the adjustment of future energy structure and the development of chemical industry. At present, my country has become the world's largest formaldehyde producer and consumer. By 2022, the domestic demand has exceeded 2800×10 4 ton.
[0003] Formaldehyde can be produced from raw materials such as methanol, dimethyl ether, and natural gas, among which methanol-to-formaldehyde process is the most widely used. The methanol air oxidation method is divided into the silver method and the iron-molybdenum method. Compared with the silver method, the iron-molybdenum method has a low reaction temperature and a high formaldehyde concentration, and has the advantages of low cost and high output. There are many patents for the production of formaldehyde using iron-molybdenum catalysts:
[0004] For example, US4420421 describes that different raw materials, sodium molybdate, are used to achieve a methanol conversion rate of 93% to 95%, and the selectivity is increased to 92%; Patent CN105457648B prepares a catalyst containing a large number of mesopores and a certain proportion of macropores by coprecipitation, which is beneficial to the mass transfer and heat transfer of the catalyst and improves the activity of the catalyst; CN110893344B uses metallic iron, organic acid and molybdic acid as raw materials, and the iron-molybdenum catalyst prepared by coprecipitation with by-product hydrogen can achieve efficient methanol conversion at 200-350°C, but its inlet methanol concentration is low and the actual formaldehyde space-time yield is low.
[0005] However, the existing iron-molybdenum catalyst will have different degrees of catalyst deactivation as the use time increases, thus affecting the activity and service life of the catalyst. The main reason for catalyst deactivation is the loss of molybdenum element, which leads to the reduction of catalyst activity and the deep oxidation reaction, which generates CO and CO2 and reduces the selectivity of the catalyst. In the above prior art, the activity and selectivity of the catalyst are improved by adding additives, but the problem of catalyst life is not fundamentally solved. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a catalyst for preparing formaldehyde, wherein the octahedrons in the lattice formed by the FeO6 octahedron group are partially distorted by ultrasonic heating to generate octahedral defects and form channels. Excessive Mo at the interface between Fe2(MoO4)3 and MoO3 phases will form MoO3 embedded in the lattice gap of the catalyst Fe2(MoO4)3, resulting in a certain degree of lattice distortion. The Mo entering the channel 6+The combination of ions and defective octahedral oxygen vacancies forms an octa-coordination, which increases the lattice defects of the catalyst and adjusts the cyclic oxidizability and dispersibility of the catalyst surface, so that the catalyst exhibits better catalytic activity; at the same time, by introducing benzene / sodium acetate, the large π bond of the benzene ring forms a conjugated system with the catalyst octahedron; secondly, the sulfur element can combine with the oxygen vacancies on some octahedrons, inhibiting the deep oxidation reaction of formaldehyde to a certain extent and improving the selectivity of the catalyst.
[0007] In order to solve the above technical problems and achieve the above invention objectives, the present invention adopts the following technical solutions:
[0008] A method for preparing a catalyst for preparing formaldehyde comprises the following steps:
[0009] a) adding an aqueous solution containing a molybdenum salt, sodium sulfide, an iron-containing substance, a cerium salt, a nickel salt, and an aromatic compound into a reaction kettle in parallel and stirring the mixture thoroughly;
[0010] b) controlling the pH value to 1.0 to 3.0, preferably 1.5 to 2.8, and controlling the temperature of the reactor to 50 to 100° C. for coprecipitation;
[0011] c) transferring the reaction solution after the coprecipitation to an ultrasonic generator for ultrasonic and heating treatment;
[0012] d) aging the reaction solution after ultrasonication at 50° C. to 100° C., and then filtering and washing to obtain a filter cake;
[0013] e) drying the filter cake;
[0014] f) The catalyst powder obtained after drying is subjected to molding treatment and calcined at 400° C. to 560° C. to obtain a molded catalyst.
[0015] In the preparation method, in step a), the molybdenum salt comprises one or more of ammonium polymolybdate, molybdenum trioxide, molybdic acid and molybdenum disulfide, preferably ammonium polymolybdate;
[0016] The iron-containing substance includes one or more of ferric chloride, ferric nitrate, ferric oxide, and iron powder, preferably ferric chloride and / or ferric nitrate;
[0017] The cerium salt is preferably cerium nitrate, and the nickel salt is preferably nickel nitrate;
[0018] The aromatic compounds are sodium benzoate and sodium phenylacetate.
[0019] In the step c), the frequency range of the ultrasonic wave in the ultrasonic treatment is 30kHz to 50kHz, the heating temperature is controlled at 30 to 80°C, and the treatment time is 0.1 to 2h.
[0020] In the step d), the aging time is 24 to 48 hours;
[0021] In the step e), the filter cake is dried at 50°C to 100°C for 10 to 28 hours, and then dried at 100°C to 150°C for 15 hours to 30 hours to obtain a catalyst powder;
[0022] In the step f), calcining for 5 to 20 hours;
[0023] The molding method includes but is not limited to extrusion, tableting, rolling and the like; the shape of the obtained molded catalyst includes but is not limited to strips, cylinders, hollow cylinders, spherical particles and the like;
[0024] For example, a suitable extrusion molding method includes the following steps: adding a pore-forming agent and a binder to the catalyst powder for extrusion molding to obtain strip particles. The pore-forming agent is one or more of sesbania powder, cellulose, hydroxymethyl cellulose, and polyvinyl alcohol, and the amount of the pore-forming agent is 1% to 6% of the mass of the catalyst powder. The binder is one or more of water, glycerol, ethanol, graphite, stearic acid, magnesium stearate, and zinc stearate, preferably one or more of water, glycerol, graphite, and magnesium stearate, and the amount of the binder is 8% to 15% of the mass of the catalyst powder;
[0025] For example, a suitable tableting method includes the following steps: adding a pore-forming agent and a lubricant to the catalyst powder for tableting to obtain cylindrical or hollow cylindrical particles. The pore-forming agent is one or more of sesbania powder, cellulose, polyethylene, polypropylene, and polyvinyl chloride, preferably sesbania powder and / or cellulose, and the amount of the pore-forming agent is 1% to 5% of the mass of the catalyst powder. The lubricant is one or more of stearic acid, magnesium stearate, zinc stearate, and graphite, preferably one or more of magnesium stearate, zinc stearate, and graphite, and the amount of the lubricant is 0.1% to 1% of the mass of the catalyst powder;
[0026] For example, a suitable rolling forming method comprises the following steps: adding a pore-forming agent and a binder to the catalyst powder, and rolling forming with a spherical carrier. The pore-forming agent is one or more of sesbania powder, cellulose, polyvinyl alcohol, polyvinyl pyrrolidone, starch, and pullulan, preferably one or more of sesbania powder, polyvinyl pyrrolidone and starch, and the amount of the pore-forming agent is 1% to 5% of the mass of the catalyst powder. The binder is one or more of water, ethanol, ethylene glycol, and glycerol, preferably one or more of water, ethanol and glycerol, and the amount of the binder is 20% to 35% of the catalyst powder. The spherical carrier is preferably a porous alumina carrier with a diameter of 2.3 to 3.5 mm, and the amount is 50% to 70% of the mass of the catalyst powder.
[0027] A catalyst for preparing formaldehyde is prepared by the above method, preferably, wherein: the Mo / Fe molar ratio is 0.5-1.0:1; the S / Fe molar ratio is in the range of 0.1-2.0; the Ce / Fe molar ratio is in the range of 0.1-0.4; the Ni / Fe molar ratio is in the range of 0.1-0.5; and the aromatic compound / Fe molar ratio is in the range of 0.5-1.1.
[0028] A method for preparing aldehydes by alcohol oxidation, using the above catalyst, wherein:
[0029] The reaction temperature is 320-420°C; the reaction pressure is 0.05-0.3 MPa absolute pressure; the gas raw material volume space velocity is 7000-12000 h -1 The gas raw material includes methanol, diluent gas and O2, wherein the diluent gas is an inert gas, preferably N2. The molar ratio between the gases is 1:9-12:1-3;
[0030] The catalyst is pretreated before use; preferably, the pretreatment comprises the following steps: the catalyst is heated at a volume space velocity of 5000 to 10000 h -1 In an atmosphere of air or O2 / N2 mixed gas, the temperature is raised to 200-400°C at a rate of 1-20°C / min and maintained for 30-180min. -1 N2 purge for 1 to 180 minutes.
[0031] The beneficial effects of the present invention are:
[0032] The catalyst manufactured by the method of the present invention can effectively solve the problem of deep oxidation reaction of the catalyst in the previous process method, while improving the activity and stability of the catalyst and extending the life of the catalyst. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below by examples, but is not limited thereto.
[0034] In the present invention, the equipment and raw materials used, unless otherwise specified, are all purchased from the market.
[0035] Example 1
[0036] 0.07 mol of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O2·4H2O), 1 mol of ferric chloride hexahydrate (chemical formula: FeCl3·6H2O), 1 mol of sodium sulfide (chemical formula: Na2S), 0.3 mol of nickel nitrate (chemical formula: Ni(NO3)3), 0.1 mol of cerium nitrate (chemical formula: Ce(NO3)3), and 0.8 mol of sodium phenylacetate were dissolved in 1000 g of deionized water, stirred thoroughly, and added into the reactor in parallel, the temperature of the solution in the reactor was maintained at 90°C, and the pH value was adjusted to 2.0 for coprecipitation.
[0037] The reaction solution was subjected to ultrasonic treatment (Merritek Technology, model UC-6200, 40kHz, 30°C) for 1.5h, and then kept at 90°C for 28h after ultrasonic treatment. After filtration and washing, the filter cake was dried at 90°C for 24h and then at 120°C for 20h. After drying, a block solid was obtained, which was crushed to obtain particles of 30-60 mesh.
[0038] Take 50g of 30-60 mesh granules, add 2.5g of pore-forming agent sesbania powder and 0.5g of lubricant magnesium stearate, mix well, and form into hollow cylindrical granules by tablet press. The formed granules are calcined at 420°C for 5h to obtain a catalyst.
[0039] 25g of catalyst was loaded into a 50cm long reactor, where the reaction tube was a 25mm stainless steel reaction tube. The catalyst pretreatment process was as follows: firstly, air was introduced at a volume space velocity of 8000h -1 The temperature of the reaction tube was heated from room temperature to 250°C at a heating rate of 5°C / min and maintained for 120 min, then switched to nitrogen purge for 180 min at a purge volume space velocity of 2000 h -1 .
[0040] After the catalyst pretreatment was completed, methanol: oxygen: nitrogen: water = 1:1.3:10:0.13 (molar ratio), volume space velocity 10000h -1 The oxidation reaction was carried out under the conditions of (standard state), temperature of 380°C and normal pressure for 100 hours. The selectivity of formaldehyde was 95.5% and the conversion rate of methanol was 97.8%.
[0041] Example 2
[0042] 0.11 mol of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O2·4H2O), 1 mol of ferric chloride hexahydrate (chemical formula: FeCl3·6H2O), 2 mol of sodium sulfide (chemical formula: Na2S), 0.5 mol of nickel nitrate (chemical formula: Ni(NO3)3), 0.2 mol of cerium nitrate (chemical formula: Ce(NO3)3), and 1.1 mol of sodium phenylacetate were dissolved in 1000 g of deionized water, stirred thoroughly, and added into the reactor, the solution temperature in the reactor was maintained at 90°C, and the pH value was adjusted to 2.0 for coprecipitation.
[0043] The reaction solution was subjected to ultrasonic treatment for 1.5 h (Merritek Technology, model UC-6200, 40 kHz, 30°C), and maintained at 90°C for 28 h after ultrasonic treatment. Filter and wash, and the filter cake was dried at 90°C for 24 h and then at 120°C for 20 h. After drying, a block solid was obtained, which was crushed to obtain particles of 30 to 60 mesh.
[0044] Take 50g of 30-60 mesh granules, add 2.5g of pore-forming agent sesbania powder and 0.5g of lubricant magnesium stearate, mix well, and form into hollow cylindrical granules by tablet press. The formed granules are calcined at 420°C for 5h to obtain a catalyst.
[0045] 25g of catalyst was loaded into a 50cm long reactor, where the reaction tube was a 25mm stainless steel reaction tube. The catalyst pretreatment process was as follows: firstly, air was introduced at a volume space velocity of 8000h -1 The temperature of the reaction tube was heated from room temperature to 250°C at a heating rate of 5°C / min and maintained for 120 min, then switched to nitrogen purge for 180 min at a purge volume space velocity of 3000 h -1 .
[0046] After the catalyst pretreatment was completed, methanol: oxygen: nitrogen: water = 1:1.3:10:0.13 (molar ratio), volume space velocity 10000h -1 The oxidation reaction was carried out under the conditions of (standard state), temperature of 380°C and normal pressure for 100 hours. The selectivity of formaldehyde was 95.0% and the conversion rate of methanol was 98.8%.
[0047] Example 3
[0048] 0.14 mol of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O2·4H2O)), 1 mol of ferric chloride hexahydrate (chemical formula: FeCl3·6H2O), 0.1 mol of sodium sulfide (chemical formula: Na2S), 0.1 mol of nickel nitrate (chemical formula: Ni(NO3)3), 0.4 mol of cerium nitrate (chemical formula: Ce(NO3)3, 0.5 mol of sodium phenylacetate were dissolved in 1000 g of deionized water, fully stirred, and added into the reactor in a stream. The temperature of the solution in the reactor was kept at 90°C, and the pH value was adjusted to 2.0 for coprecipitation.
[0049] The reaction solution was subjected to ultrasonic treatment for 1.5 h (Merritek Technology, model UC-6200, 40 kHz, 30°C), and maintained at 90°C for 28 h after ultrasonic treatment. Filter and wash, and the filter cake was dried at 90°C for 24 h and then at 120°C for 20 h. After drying, a block solid was obtained, which was crushed to obtain particles of 30 to 60 mesh.
[0050] Take 50g of 30-60 mesh granules, add 2.5g of pore-forming agent sesbania powder and 0.5g of lubricant magnesium stearate, mix well, and form into hollow cylindrical granules by tablet press. The formed granules are calcined at 420°C for 5h to obtain a catalyst.
[0051] 25g of catalyst was loaded into a 50cm long reactor, where the reaction tube was a 25mm stainless steel reaction tube. The catalyst pretreatment process was as follows: firstly, air was introduced at a volume space velocity of 8000h -1 The temperature of the reaction tube was heated from room temperature to 250°C at a heating rate of 5°C / min and maintained for 120 min, then switched to nitrogen purge for 180 min at a purge volume space velocity of 2000 h -1 .
[0052] After the catalyst pretreatment was completed, methanol: oxygen: nitrogen: water = 1:1.3:10:0.13 (molar ratio), volume space velocity 10000h -1 The oxidation reaction was carried out under the conditions of (standard state), temperature of 380°C and normal pressure for 100 hours. The selectivity of formaldehyde was 94.5% and the conversion rate of methanol was 98.1%.
[0053] Comparative Example 1
[0054] Dissolve 0.07mol of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O2·4H2O), 1mol of ferric chloride hexahydrate (chemical formula: FeCl3·6H2O), 0.3mol of nickel nitrate (chemical formula: Ni(NO3)3), and 0.1mol of cerium nitrate (chemical formula: Ce(NO3)3) in 1000g of deionized water, stir well, and add them into the reactor. Keep the temperature of the solution in the reactor at 90℃, adjust the pH value to 2.0 for coprecipitation, and then keep 90℃ for stirring and aging for 28h. Filter and wash, and dry the filter cake at 90℃ for 24h and then at 120℃ for 20h. After drying, a block solid is obtained, which is crushed to obtain 30-60 mesh particles. Take 50g of 30-60 mesh particles, add 2.5g of pore-forming agent sesbania powder and 0.5g of lubricant magnesium stearate, mix well, and use a tablet press to form hollow cylindrical particles. The formed particles were calcined at 420°C for 5 h to obtain a catalyst.
[0055] The oxidation reaction was carried out for 100 hours in the same manner as in Example 1. The selectivity of formaldehyde was 90.5%, and the conversion rate of methanol was 92.8%.
[0056] Comparative Example 2
[0057] Dissolve 0.07 mol of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O2·4H2O), 1 mol of ferric chloride hexahydrate (chemical formula: FeCl3·6H2O), 0.3 mol of nickel nitrate (chemical formula: Ni(NO3)3), and 0.1 mol of cerium nitrate (chemical formula: Ce(NO3)3) in 1000 g of deionized water respectively, stir well, and add them into the reactor in a stream, keep the solution temperature in the reactor at 90°C, and adjust the pH value to 2.0 for co-precipitation.
[0058] The reaction solution was subjected to ultrasonic treatment for 1.5 h (Merritek Technology, model UC-6200, 40 kHz, 30°C), and maintained at 90°C for 28 h after ultrasonic treatment. Filter and wash, and the filter cake was dried at 90°C for 24 h and then at 120°C for 20 h. After drying, a block solid was obtained, which was crushed to obtain particles of 30 to 60 mesh.
[0059] Take 50g of 30-60 mesh granules, add 2.5g of pore-forming agent sesbania powder and 0.5g of lubricant magnesium stearate, mix well, and form into hollow cylindrical granules with a tablet press. The formed granules are calcined at 420°C for 5h to obtain a catalyst.
[0060] The oxidation reaction was carried out for 100 hours in the same manner as in Example 1. The selectivity of formaldehyde was 92.5%, and the conversion rate of methanol was 93.8%.
[0061] Comparative Example 3
[0062] Dissolve 0.07mol of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O2·4H2O), 1mol of ferric chloride hexahydrate (chemical formula: FeCl3·6H2O), 1mol of sodium sulfide (chemical formula: Na2S), 0.3mol of nickel nitrate (chemical formula: Ni(NO3)3), 0.1mol of cerium nitrate (chemical formula: Ce(NO3)3), and 0.8mol of sodium phenylacetate in 1000g of deionized water, stir them fully, and add them into the reactor in parallel. Keep the temperature of the solution in the reactor at 90℃, adjust the pH value to 2.0 for coprecipitation, and then keep 90℃ for stirring and aging for 28h. Filter and wash, dry the filter cake at 90℃ for 24h and then at 120℃ for 20h. After drying, obtain a block solid, crush it, and obtain 30-60 mesh particles. Take 50g of 30-60 mesh granules, add 2.5g of pore-forming agent sesbania powder and 0.5g of lubricant magnesium stearate, mix well, and form into hollow cylindrical granules with a tablet press. The formed granules are calcined at 420°C for 5h to obtain a catalyst.
[0063] The oxidation reaction was carried out for 100 hours in the same manner as in Example 1. The selectivity of formaldehyde was 91.5%, and the conversion rate of methanol was 93.8%.
[0064] Comparative Example 4
[0065] Dissolve 0.07 mol of ammonium heptamolybdate (chemical formula: (NH4)6Mo7O2·4H2O)), 1 mol of ferric chloride hexahydrate (chemical formula: FeCl3·6H2O), 1 mol of sodium sulfide (chemical formula: Na2S), 0.3 mol of nickel nitrate (chemical formula: Ni(NO3)3), and 0.1 mol of cerium nitrate (chemical formula: Ce(NO3)3) in 1000 g of deionized water respectively, stir well, and add them into the reactor in parallel, keep the solution temperature in the reactor at 90°C, and adjust the pH value to 2.0 for co-precipitation.
[0066] The reaction solution was subjected to ultrasonic treatment for 1.5 h (Merritek Technology, model UC-6200, 40 kHz, 30°C), and maintained at 90°C for 28 h after ultrasonic treatment. Filter and wash, and the filter cake was dried at 90°C for 24 h and then at 120°C for 20 h. After drying, a block solid was obtained, which was crushed to obtain particles of 30 to 60 mesh.
[0067] Take 50g of 30-60 mesh granules, add 2.5g of pore-forming agent sesbania powder and 0.5g of lubricant magnesium stearate, mix well, and form into hollow cylindrical granules with a tablet press. The formed granules are calcined at 420°C for 5h to obtain a catalyst.
[0068] The oxidation reaction was carried out for 100 hours in the same manner as in Example 1. The selectivity of formaldehyde was 92.1%, and the conversion rate of methanol was 93.6%.
[0069] By comparing Example 1 with Comparative Examples 1.2.3.4, it can be seen that by adding sodium sulfide inorganic matter and aromatic organic compounds and adopting ultrasonic heating, the problem of deep oxidation reaction of the catalyst in the previous process method can be effectively solved, while the activity and stability of the catalyst can be improved and the life of the catalyst can be extended.
Claims
1. A method for preparing a catalyst for preparing formaldehyde, comprising the following steps: a) adding an aqueous solution containing a molybdenum salt, sodium sulfide, an iron-containing substance, a cerium salt, a nickel salt, and an aromatic compound into a reaction kettle in parallel and stirring the mixture thoroughly; b) controlling the reaction conditions to carry out coprecipitation; c) subjecting the reaction solution after the coprecipitation to ultrasonic and heating treatment; d) aging the reaction solution after ultrasonication, and then filtering and washing to obtain a filter cake; e) drying the filter cake; f) performing molding treatment and calcining to obtain a molded catalyst.
2. The preparation method according to claim 1, in step a), the molybdenum salt comprises one or more of ammonium polymolybdate, molybdenum trioxide, molybdic acid and molybdenum disulfide; The iron-containing substance includes one or more of ferric chloride, ferric nitrate, ferric oxide, and iron powder; The cerium salt is cerium nitrate, and the nickel salt is nickel nitrate; The aromatic compounds are sodium benzoate and sodium phenylacetate.
3. According to the preparation method of claim 1 or 2, in step b), the pH value is between 1.0 and 3.0 and the temperature is between 50 and 100°C.
4. The preparation method according to any one of claims 1 to 3, wherein in step c), the ultrasonic frequency range of the ultrasonic treatment is 30 kHz to 50 kHz, the heating temperature is 30 to 80°C, and the treatment time is 0.1 to 2 h.
5. The preparation method according to any one of claims 1 to 4, wherein in step d), aging is performed at 50°C to 100°C for 24 to 48 hours.
6. The preparation method according to any one of claims 1 to 5, wherein in step e), the filter cake is dried at 50°C to 100°C for 10 to 28 hours, and then dried at 100°C to 150°C for 15 hours to 30 hours to obtain a catalyst powder.
7. The preparation method according to any one of claims 1 to 6, wherein in step f), the mixture is calcined at 400°C to 560°C for 5 to 20 hours.
8. A catalyst for preparing formaldehyde obtained by the preparation method according to any one of claims 1 to 7, preferably, wherein: The molar ratio of Mo / Fe is 0.5 to 1.0:1; the molar ratio of S / Fe is 0.1 to 2.0; the molar ratio of Ce / Fe is 0.1 to 0.4; the molar ratio of Ni / Fe is 0.1 to 0.5; and the molar ratio of aromatic compound to Fe is 0.5 to 1.
1.
9. A method for preparing aldehydes by oxidation of alcohols, using the catalyst obtained by the preparation method according to any one of claims 1 to 7 or the catalyst according to claim 8, wherein: The reaction temperature is 320-420°C; the reaction pressure is 0.05-0.3 MPa absolute pressure; the gas raw material volume space velocity is 7000-12000 h -1 The gas raw material includes methanol, dilution gas and O2, and preferably, the dilution gas is N2.
10. The method according to claim 9, wherein: The molar ratio of methanol, diluent gas and O2 is 1:9-12:1-3.
Citation Information
Patent Citations
Ferromolybdenum Formaldehyde Synthesis Catalyst and Its Preparation Method
CN105457648B
A methanol oxidation catalyst for formaldehyde production, its preparation and application
CN110893344B
Process for the preparation of catalysts based on iron and molybdenum oxides
US4420421A
Iron-molybdenum catalyst for formaldehyde synthesis through methanol oxidation as well as preparation method and application
CN106693981A
Catalyst for preparing aldehyde by oxidation method as well as preparation method and application of catalyst
CN115487818A